Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1250 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plagioscion squamosissimus (Heckel, 1840)", { "or" : [ "Country is Brazil", "Country is Guyana", "Country is Peru", "Country is Colombia", "Country is Bolivia (Plurinational State of)", "Country is Ecuador", "Country is Suriname", "Country is Venezuela (Bolivarian Republic of)" ] } ] } The dataset includes 1250 records from 35 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0021519-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences